2020
DOI: 10.3390/jpm10030133
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Association Analysis of ABCB1 rs1045642 and ABCB1 rs4148738 with Non-Major Bleeding Risk in Atrial Fibrillation Patients Treated with Dabigatran or Apixaban

Abstract: (1) Background: The approach of bleeding complications in patients treated with non-vitamin K oral anticoagulants (NOACs) represents an important issue in clinical practice. Both dabigatran and apixaban are substrates for P-glycoprotein and, therefore, ABCB1 gene variations may be useful in individualizing NOACs treatment, especially in high-risk patients. (2) Methods: ABCB1 rs1045642 and rs4148738 were determined in 218 atrial fibrillation patients treated with dabigatran or apixaban (70.94 ± 9.04 years; 51.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 51 publications
1
13
1
Order By: Relevance
“…We also found an association of the ABCB1 c.2482‐2236G>A SNV with a decreased bleeding risk in apixaban users. This variant has been found to be associated with bleeding in one earlier study, 10 while other studies have not been able to confirm the association 19,34 …”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…We also found an association of the ABCB1 c.2482‐2236G>A SNV with a decreased bleeding risk in apixaban users. This variant has been found to be associated with bleeding in one earlier study, 10 while other studies have not been able to confirm the association 19,34 …”
Section: Discussionmentioning
confidence: 91%
“…This variant has been found to be associated with bleeding in one earlier study, 10 while other studies have not been able to confirm the association. 19,34 So far, the most extensive investigation of the pharmacogenomics of DOACs has been the genome-wide association study of Paré et al focusing on dabigatran users. 13 The study found association of the CES1 rs2244613 SNV with a decreased risk of bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dabigatran etexilate is a substrate of P-glycoprotein encoded by the ABCB1 gene. ABCB1 variants are potential factors affecting thromboembolic events in dabigatran users and bleeding events 18 . Earlier studies have found associations between genetic variability and plasma levels of direct oral anticoagulants 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Dabigatran etexilate is a substrate of P-glycoprotein encoded by the ABCB1 gene. ABCB1 variants are potential factors affecting thromboembolic events in dabigatran users and bleeding events [27]. Earlier studies have found associations between genetic variability and plasma levels of direct oral anticoagulants [17,28].…”
Section: Discussionmentioning
confidence: 99%